A rare glycoalkaloid biosynthetic pathway from wild potato unlocks genetic routes to Colorado potato beetle resistance - Ryota Akiyama; Yuki Ikeyama; Hyoung Jae Lee; Naoyuki Umemoto; Kenji Asano; Tetsuya Mori; Toshiya Muranaka; Kazuki Saito; Yukihiro Sugimoto; Masaharu Mizutani (Proceedings of the National Academy of Sciences, 2026)
Plants in the family Solanaceae produce steroidal glycoalkaloids (SGAs), specialized metabolites that are toxic to consumers while providing protection against herbivores. The Colorado potato beetle (CPB) is a major foliar pest of potatoes, and the wild species Solanum chacoense PI458310 displays resistance through the accumulation of the specific SGAs leptine I/II, the C-23-acetoxylated derivatives of α-chaconine/α-solanine. Although these leptines and their presumed C-23-hydroxylated precursors, leptinine I/II, have been recognized for decades, their biosynthetic routes have remained unresolved. In this study, we show that leptinines and leptines do not originate from direct modificfation of α-chaconine/α-solanine, but instead arise from earlier transformations of spirosolane-type precursors. We identified Sc23DOX , a spirosolane C-23 hydroxylase, and Sc23ACT , a 23- O -acetyltransferase, and demonstrated in vitro that these enzymes convert α/β-solamarine into 23-hydroxy and 23- O -acetyl intermediates, which are subsequently processed into leptinines and leptines by the ring-rearrangement enzymes Dioxygenase for Potato Solanidane synthesis (DPS), Reductase for Potato Glycoalkaloid biosynthesis 1 (RPG1), and RPG2. Notably, these C-23 hydroxylation and O-acetylation reactions parallel the initial steps of α-tomatine detoxification during fruit ripening in tomato ( Solanum lycopersicum ). Moreover, when Sc23DOX and Sc23ACT were expressed heterologously in cultivated potato, the plants produced leptinines and leptines de novo. Genomic and transcriptomic analyses further revealed that many cultivated potatoes ( Solanum tuberosum ) retain apparently functional 23DOX and 23ACT orthologues, and that expression of 23DOX alone can restore leptine biosynthesis in certain cultivars. Collectively, these findings clarify the leptinine/leptine biosynthetic pathway, illustrate the co-option of a detoxification-related module into a defense system, and provide a genetic basis for breeding or engineering CPB-resistant potatoes.